Mengembangkan Kecerdasan Eksistensial Melalui Kegiatan Bermain Peran Pada Anak Usia Dini - Nur Asiah Lubis; Dhinanda Aulia; Aulia Khairani; Masganti Sit (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
Existential intelligence refers to an individual's ability to understand the meaning of life, explore existential goals, and build meaningful connections in everyday life. This research aims to examine the influence of role-playing activities on the development of existential intelligence in early childhood. This research uses a descriptive qualitative approach with participatory observation techniques and in-depth interviews with children involved in role-playing activities in early childhood education environments. Research shows that role-playing activities can significantly develop children's existential intelligence. This research shows an increased ability to interpret and deal with everyday life experiences through roles played. Children develop a deeper understanding of social relationships, values, and ways to overcome challenges in life. These findings show the importance of expanding the approach to early childhood education to include role-playing activities to facilitate the development of existential intelligence. The practical implication of this research is that educators and parents can consider integrating role-playing activities in the early childhood curriculum as a strategy to support children's holistic development and the role of parents and teachers in working together to increase children's existential intelligence.